Integrating Scientific Studies and Education: A Strategic Approach to Enhancing Learning Quality and Innovation in Higher Education - Wang, Hong; Yujie Wei (Ilmu Inovasi Nusantara, 2025)
To accelerate the development of a strong nation in education, science, and technology while achieving self-reliance in high-level scientific and technological advancements, the integrated